Kajian tentang Metode Istinbath Ahkam dalam Menghadapi Tantangan Ekonomi Syariah di Era Globalisasi - Zulfa, Aini Yatuz; Nuraeni, Neni (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The method of istinbath ahkam plays a strategic role as an Islamic legal approach in addressing the challenges of Islamic economics in the era of globalization. Positioned as an essential instrument, it enables the formulation of laws that are adaptive to modern economic dynamics while upholding the principles of maqashid al-shariah. This study employs a qualitative approach based on literature reviews of classical and contemporary sources. The findings show that istinbath ahkam can produce contextual and applicable legal solutions in line with global economic developments, including cross-border trade, sustainability, and market stability. These insights highlight the need to strengthen the istinbath ahkam methodology in Islamic economics so that legal rulings can serve as effective guidelines amid global complexities.